High temperature initiation and propagation of cracks in 12%Cr-steel turbine disks - S. Foletti; A. Lo Conte; S. Salgarollo; F. Bassi; A. Riva (Fracture and Structural Integrity)
This work aims to study the crack propagation in 12%Cr steel for turbine disks. Creep Crack Growth (CCG) tests on CT specimens have been performed to define the proper fracture mechanics which describes the initiation of the crack propagation and the crack growth behaviour for the material at high temperature. Results have been used to study the occurrence of crack initiation on a turbine disk at the extreme working temperature and stress level experienced during service, and validate the use of C* integral in correlating creep growth rate on the disk component, in case C* is numerically calculated through FEM analysis or calculated by the use of reference stress concept.